2002
DOI: 10.1093/humrep/17.12.3027
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous albumin for preventing severe ovarian hyperstimulation syndrome: a Cochrane review

Abstract: This Cochrane review shows a clear benefit from administration of i.v. albumin at the time of oocyte retrieval in prevention of severe OHSS in high-risk cases. Whether the number needed to treat would justify the routine use of albumin infusion in cases at risk of severe OHSS needs to be judged by clinical decision-makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…This was followed by a number of RCTs of a small number of patients deemed to be at risk of OHSS on the basis of parameters of ovarian response, which appeared to show a reduction in the incidence of severe OHSS in the group receiving albumin. In 2002, a Cochrane meta-analysis [17] of 5 RCTs (n = 378) showed a significant reduction in the incidence of severe OHSS in women receiving IV albumin (OR = 0.28, 95% CI = 0.11-0.73). However, a systematic review by Delvigne and Rozenberg [2] , including several studies that had not been considered in the previous Cochrane review, found no significant difference in the incidence of OHSS between the patients receiving albumin (8.3%) and the controls (14.6%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was followed by a number of RCTs of a small number of patients deemed to be at risk of OHSS on the basis of parameters of ovarian response, which appeared to show a reduction in the incidence of severe OHSS in the group receiving albumin. In 2002, a Cochrane meta-analysis [17] of 5 RCTs (n = 378) showed a significant reduction in the incidence of severe OHSS in women receiving IV albumin (OR = 0.28, 95% CI = 0.11-0.73). However, a systematic review by Delvigne and Rozenberg [2] , including several studies that had not been considered in the previous Cochrane review, found no significant difference in the incidence of OHSS between the patients receiving albumin (8.3%) and the controls (14.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for the putative effect of albumin in preventing OHSS have been proposed: albumin is thought to prevent the development of OHSS by increasing plasma oncotic pressure and binding of the vasoactive mediators of ovarian origin, such as VEGF [10,12,17] , but this has not been substantiated. Because capillary permeability is compromised in patients with OHSS, the duration of the oncotic effect would be insufficient to prevent OHSS [2] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its efficacy is still a matter of debate. A review article published in 2002 [30] included five RCTs and evaluated the use of albumin in 193 women and 185 controls. The odds ratio for OHSS in the group treated with albumin was 0.28 (95%IC 0.11-0.73).…”
Section: Albumin Administrationmentioning
confidence: 99%